2013
DOI: 10.1016/j.ijfoodmicro.2013.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination efficiency of high power ultrasound in the fruit and vegetable industry, a review

Abstract: Decontamination of fresh fruits and vegetables is an important unsolved technological problem. The main focus of this review is to summarize and synthesize the results of studies and articles about ultrasonic processing which can be adapted to the wash water decontamination process for fruits and vegetables. This review will also provide an overview about the importance of an effective wash water decontamination process in fruits and vegetables, the increase of foodborne outbreaks caused by fresh fruits and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(93 citation statements)
references
References 64 publications
0
88
1
4
Order By: Relevance
“…Disruption of the cellular structure and functional components of microbial cells lead to cell lysis. Other possible mechanisms are associated with the localized heating (5500°C), high pressure (500 MPa) and formation of free radicals (H+, O − , OH − , HO 2 − and H 2 O 2 ), which results from the sonolysis of water present in liquids (Bilek & Turantas, 2013;Tiwari & Mason, 2012).…”
Section: Food Safetymentioning
confidence: 99%
“…Disruption of the cellular structure and functional components of microbial cells lead to cell lysis. Other possible mechanisms are associated with the localized heating (5500°C), high pressure (500 MPa) and formation of free radicals (H+, O − , OH − , HO 2 − and H 2 O 2 ), which results from the sonolysis of water present in liquids (Bilek & Turantas, 2013;Tiwari & Mason, 2012).…”
Section: Food Safetymentioning
confidence: 99%
“…Recently, the food industry has also discovered ultrasound technology which has a variety of applications in processing, preservation, and extraction (Chemat et al, 2011). Bilek and Turantaş (2013) reported that combination of ultrasound and aqueous sanitizers effectively reduced microbial contamination in fresh fruits and vegetables. To enhance its efficacy, however, it would most likely have to be used in conjunction with heat treatment (thermosonication) (Awad et al, 2012;Chemat et al, 2011;Mansur and Oh, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous studies on the antimicrobial efficacy of ultrasound in the food industry, which have been reviewed by Awad et al (2), Bilek et al (14), and de São José et al (3). Unfortunately, in order to determine the impact of ultrasound treatment, most of these studies employed the classical plate count method which is a retrospective method because of the long incubation time.…”
mentioning
confidence: 99%